The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2407-13-128
|View full text |Cite
|
Sign up to set email alerts
|

αB-crystallin stimulates VEGF secretion and tumor cell migration and correlates with enhanced distant metastasis in head and neck squamous cell carcinoma

Abstract: BackgroundαB-crystallin is able to modulate vascular endothelial growth factor (VEGF) secretion. In many solid tumors VEGF is associated with angiogenesis, metastasis formation and poor prognosis. We set out to assess whether αB-crystallin expression is correlated with worse prognosis and whether this is related to VEGF secretion and cell motility in head and neck squamous cell carcinoma (HNSCC).MethodsαB-crystallin expression was determined immunohistochemically in tumor biopsies of 38 HNSCC patients. Locoreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
(55 reference statements)
1
32
0
Order By: Relevance
“…For example, Shi et al8 found that CRYAB promoted the invasion and metastasis of colorectal cancer cells via EMT. Consistently, Chantal et al suggested CRYAB as a useful biomarker to help fine‐tune treatment in head and neck squamous cell carcinoma, possibly by targeting CRYAB‐mediated cell motility 9. Obviously, these findings provide evidence delineating the pivotal role of CRYAB in cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, Shi et al8 found that CRYAB promoted the invasion and metastasis of colorectal cancer cells via EMT. Consistently, Chantal et al suggested CRYAB as a useful biomarker to help fine‐tune treatment in head and neck squamous cell carcinoma, possibly by targeting CRYAB‐mediated cell motility 9. Obviously, these findings provide evidence delineating the pivotal role of CRYAB in cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 76%
“…Interestingly, recent studies have revealed that CRYAB is aberrantly overexpressed in various types of cancer, and its expression could promote cell invasion and metastasis 8, 9, 10. For example, Shi et al8 found that CRYAB promoted the invasion and metastasis of colorectal cancer cells via EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the expression rates of integrin alpha-3 for locoregional and ITGB4 for haematogenous dissemination and, therefore, cancer cell motility and anchorage-independent survival, which are vital for OSCC recurrence and metastasis, has previously been shown. Furthermore, the importance of integrin beta1 in HNSCC and stimulated vascular endothelial growth factor secretion by alphaB-crystallin in HNSCC was specified [100,101] . In addition to these considerations, there might be a spread of tumour-derived molecules on a subcellular level, such as micro-RNAs.…”
Section: A Discussion Of the Results From Studies On Head And Neck Camentioning
confidence: 99%
“…Overexpression of HspB5 can transform immortalized human mammary epithelial cells that can develop invasive mammary carcinomas in nude mice with basal-like breast tumor features (Moyano et al 2006 ). Consequently HspB5 can be considered as a biomarker in the diagnosis of breast cancers, especially in those with advanced grade (Ivanov et al 2008 ;Sitterding et al 2008 ;Tsang et al 2012 ). Similarly, high levels of HspB5 are associated with low survival rate in hepatocellular carcinoma (Huang et al 2013 ;Tang et al 2009 ), ovarian carcinoma (Volkmann et al 2013 ), clear cell renal cell carcinoma (Ho et al 2013 ) and head and neck squamous cell carcinoma (van de Schootbrugge et al 2013 ).…”
Section: Hspb5 Expression In Cancersmentioning
confidence: 99%